Seismic design and performance of dual structures with BRBs and semi-rigid connections. (July 2019) - Barbagallo, F.; Bosco, M.; Marino, E.M.; Rossi, P.P.
Abstract: In the past, the use of Buckling Restrained Braces (BRBs) in buildings with braced structure has been proposed to overcome the drawback of steel Concentrically Braced Frames (CBF) caused by the low dissipative cyclic behaviour of conventional buckling braces. The structure is conceived so that a few braced frames resist the entire seismic force and all the other frames sustain gravity loads only. According to the design practice adopted in European countries, all the beam-to-column connections are usually perfectly pinned. The use of these connections leads to low-redundant systems, which tend to form soft storey collapse mechanisms. The concentration of drift demand precludes the full exploitation of the deformation capacity of all the BRBs of the frame and partially reduces the benefit that may derive from these devices. A more effective structural system may be obtained by coupling frames with BRBs with frames with semi-rigid connections. In fact, the frame with semi-rigid connections provides a residual lateral stiffness after yielding of BRBs and thus promotes a more uniform distribution of the drift demand along the height of the building. This paper investigates the seismic performance of dual steel systems with BRBs and semi-rigid connections. A set of frames is designed considering several values of the behaviour factor and the response of the obtained frames is determined by nonlinear dynamic analysis. Then, the behaviour factor that allows the frames to meet the performance objectives of Eurocode 8 is determined. The seismic performance of the frames is assessed in terms of ductility demand-to-capacity ratio of dissipative members, in terms of strength demand-to-capacity ratio of non-dissipative members, and residual drifts. Highlights: The paper proposes a structural system alternative to the traditional CBFs. A design procedure is formulated in consistency with Eurocode 8. The behavior factor q for the determination of the seismic design force is provided. The effectiveness of the system is investigated by several performance parameters. Suitable configuration and stiffness of semi-rigid connections are proposed.